HAMBATAN PELAKSANAAN PROGRAM PEMBELAJARAN JARAK JAUH GURU DAN SISWA KELAS XI SMA NEGERI 1 CIMAHI MATA PELAJARAN PENJAS PADA MASA PANDEMI COVID-19 - Luthfi Nuruzzaman (Indonesian Journal for Physical Education and Sport, 2021)
In the distance learning physical education subjects, obstacles consist of internal and external factors; these obstacles certainly make the distance learning process of physical education subjects hampered. The purpose of this study was to find out what obstacles were felt by both teachers and students in implementing distance learning programs for physical education subjects during the pandemic Covid-19 at SMA Negeri 1 Cimahi. This research is a mixed-method with an exploratory approach. Data on barriers to implementing distance learning programs for physical education subjects were obtained using online interviews, online observations, and online questionnaires. The sample used in this study consisted of 1 deputy principal, two physical education teachers who teach in class XI, and 379 students simplified by random sampling technique to become 79 students, data analysis using SPSS version 22 software with validity and reliability tests. Barriers that occur in implementing distance learning programs consist of factors such as unstable internet signals, limited internet quotas, lack of understanding of physical education learning movements carried out by students. So based on the results of the study, it can be concluded that the main factors in the barriers to the physical education distance learning process that are felt by both teachers and students of class XI at SMA Negeri 1 Cimahi consist of students' external factors, namely unstable internet signals and limited internet quotas.